(untitled) - Sinzogan, Antonio A. C. (Netherlands, 2006)
Over the last decade, the economic sustainability of the cotton industry in Benin has been questioned. Low yield caused by pests and socio-economic problems have been identified as the main problems facing cotton producers, leading to low income. This thesis has addressed the technical and organisational problems of crop protection in the cotton sector in Benin
Keywords: Cotton,Fiber plants,Plants, protection of; Diseases and pests